Development Of Standardization Of Physical Test Volleyball Men’s Elite Athlete - Bahauddin, Muhammad Arja; Sudijandoko, Andun; Subagio, Irmantara; Muhammad, Muhammad; Widodo, Achmad; Khuddus, Lutfhi Abdil; Wismanadi, Himawan (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
In this research, no standardization/category provisions apply specifically to the sport of volleyball according to what is required in the sport of volleyball. Paying attention to the research survey results regarding the standardization of measuring instrument components, it is necessary to develop them from existing ones so that later, the results will be more comprehensive for male elite volleyball athletes. This research aims to create a physical fitness test for volleyball players by standardizing the sport. The type of research carried out in this research is a type of development or Research and Development (R&D), which aims to develop an existing product. The instruments used to collect information are in the form of existing or previous secondary data. They are designed to be further improved in the form of questionnaires and written questionnaires of secondary data, which will be responded to by experts. Experts select existing test items that will be corrected or eliminated by designing them properly to determine their feasibility. Then, it was developed as a comprehensive physical test item for volleyball. This study used a Likert scale analysis to analyze the research results obtained from experts and several FIVB-licensed trainers. The research results provide the results of several physical test items that will be used, including the following: In the Flexibility component, use Sit and reach; in the Speed component, use 10-meter sprint; the explosive power component uses Counter Movement Jump and Vertical Jump Running test items, Endurance component uses Bleep Test (MFT), Upper body Strength component uses Medicine ball throw, Lower body strength component uses single leg squat right & lift, in the balance component using the standing balance test item, in the speed reaction component using the Digging Agility Test item. This research concludes that standardizing elite physical test items for male elite volleyball athletes still includes general physical tests.